The Effect of Organizational Culture, Leader Behavior, Self-Efficacy, and Job Satisfaction on Job Performance of The Employees - A Hussein Fattah (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
The objective of this research is to determine the effect of organizational culture, leader behaviour, self-efficacy, and job satisfaction on the job performance of the employees of the Department of Education, Youth and Sport in Palembang city. The sample size was 120 employee and selected by random sampling techniques. The data were analyzed by path-analysis. The findings of the research show that leader behaviour, self-efficacy, and job satisfaction have the direct effect on job performance. Meanwhile, organizational culture has no direct effect on the job performance of the employees of the Department Education, Youth, and Sport in Palembang City.